(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This article analyses three ethical arguments against the use of gene-drive technologies to control for, and possibly extinguish, a particular species of vector mosquitoes (Anopheles gambiae) causing the malaria infection. We conclude that none of these arguments is truly persuasive in the specific case and, therefore, that using gene-drive technologies to suppress or eradicate the population of Anopheles gambiae could be ethically justifiable provided certain cautions referring to ecological consequences, evolutionary effects and social engagement of local communities.